Comparative methods analysis on rates of cutaneous evaporative water loss (CEWL) in cattle - Castro, Patric André [UNESP]; Campos Maia, Alex Sandro; de França Carvalho Fonsêca, Vinícius; Bernado Moura, Gustavo André; Carol de Melo Costa, Cíntia; Nascimento, Sheila Tavares; Simão, Bruno Rodrigo; Ruggieri, Ana Cláudia [UNESP]; Gomes da Silva, Roberto (Elsevier, 2021)
Closed colorimetric paper disc chambers and flow-through ventilated capsules are the most employed methods of measuring rates of local cutaneous evaporative water loss in cattle. However, we do not know if these methods show a close agreement with the total rate of cutaneous evaporative water loss derived from the weighing system (i.e., the gold standard method). We therefore combined a high-precision weighing system and flow through respirometry to accurately quantify the cutaneous evaporative water loss rates in shaded heifers, while simultaneously recording parallel data obtained from a flow-through ventilated capsule, and a closed colorimetric paper disc chamber. Least square means of the local surface-specific cutaneous evaporative water loss rate (g m−2 h−1) derived from the colorimetric paper discs and ventilated capsules show close agreement to the total rate of surface-specific cutaneous evaporative water loss (g m−2 h−1) derived from the weighing method. Likewise, fitted linear regression lines also showed that they were well correlated (e.g., R2 = 0.93 and r = 0.96 for ventilated capsule vs weighing method; and R2 = 0.81 and r = 0.91 for colorimetric paper discs vs weighing method). However, the mean square deviation revealed various sources of disagreement between the local measurements and those derived from the weighing method, in which the local rate of cutaneous evaporative water loss derived from colorimetric paper discs showed greater deviation. In conclusion, given the importance of cutaneous evaporative water loss for assessing temperature requirements and heat tolerance of cattle, our findings show large discrepancies derived from the closed colorimetric paper discs chamber when compared with parallel data derived from the gold standard method, which is sufficient to call into question previous findings obtained by employing such methods. Moreover, the flow-through ventilated capsule appears to be the most accurate method to assess the local rate of cutaneous evaporative water loss in cattle.
Keywords: Accuracy; Cutaneous surface; Evaporative heat transfer; Methods; Thermoregulation